EFFECTIVENESS OF MULTIMEDIA APPROACH IN TEACHING OF ARTS AT SECONDARY STAGE (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
Teaching is an art and a skill to be learnt. It requires the knowledge of the subject content, method techniques and teaching aids to be used for making teaching interesting and effective. The selection of teaching method and techniques depend upon the nature of the test, learning objectives on the one side and entering behavior on the other. Traditional teaching is also known as conventional teaching. Traditional teaching in art premier is one way teaching in which the teacher is more active and the students are merely passive listeners. Traditional teaching can be considered as sub-part of lecture method of teaching in which there is no use of teaching except chalkboard.